Anti-Dumping Policy as An Effort To Maintain Indonesia's Economic Sovereignty - Imanudin Affandi (Universitas Muhammadiyah Surakarta, 2023)
Anti-dumping is an effort to reduce the impact of losses due to dumping practices. In general, dumping practices are considered legal if they do not harm or damage the economy of the country that is the target market for the goods. Anti-dumping is also part of the trade defense mechanism, which is an international legal instrument provided by the World Trade Organization (WTO) to resolve dumping disputes and deal with losses arising from dumping practices in destination countries. The writing of this article uses the normative legal research method, which is research conducted by examining literature (secondary data). legal doctrine, legal theory and other literature to answer the legal issues being researched. This study intends to examine the regulations governing anti-dumping policies in Indonesia and how anti-dumping policies are carried out by the government as an effort and measure to safeguard Indonesia's economic sovereignty. The results of the research show that the regulations governing Anti-Dumping Policy in Indonesia are quite complete and practical. Likewise, the Anti-Dumping Policy carried out by the Government of Indonesia is in line with regulations in the field of international trade as ratified through Law no. 7 of 1994 concerning Ratification of the Agreement Establishing the World Trade Organization.